The relationship between Roman and local law in the Babatha and Salome Komaise archives: general analysis and three case studies on law of succession, guardianship, and marriage - Oudshoorn, Jacobine G. (Studies on the texts of the desert of Judah, 2007)
Language -- Language and references to law -- A new approach to understand the relationship between Roman and local law in the archives -- Law of succession -- Guardianship -- Marriage